Comparative Assessment Of Quality Of Life In Patients With Partial Removable Dentures Using Artificial Teeth Of Varying Hardness - Khabilov Bekhzod Nigmonovich; Yakhyoeva Gulbonu Sodikovna (International Journal of Medical Sciences And Clinical Research, 2025)
Partial tooth loss remains a common problem that negatively affects patients' quality of life. Restoration of masticatory function is typically achieved using removable dentures, while the properties of artificial teeth, particularly their hardness, can affect the wear resistance of the denture, distribution of masticatory pressure, and clinical outcomes. Data on the impact of artificial tooth hardness on the quality of life of patients with partial removable dentures is needed. The aim of the study is to compare the clinical outcomes of prosthetic treatment with partial removable dentures using artificial teeth of varying hardness by assessing patients' quality of life. Data on the impact of artificial tooth hardness on the quality of life of patients with partially removable prostheses is necessary. The purpose of the study is to compare the clinical outcomes of partially removable dentures using artificial teeth of varying hardness, assessing the quality of life of patients.